WOMAN AS ACTRESS OF TRADITIONAL PERFORMING ARTS AND GENDER JUSTICE IN EAST JAVA - Wurianto, Arif Budi (Cultural Institute University of Muhammadiyah Malang, 2017)
Main problem is whether gender justice and equality in art performance, mainly in traditional art performance, have become central issues in efforts to socialize and as a gender mainstream in Education, Law, Economy, Politic, and Social. In general and traditional art performance, woman always involved, especially the main actresses in various art performances, they are adored both as ‘diva or idol’ who are able to attract people and also are humiliated because, in some occasions, she shows her over-sensuality so that it humiliates her dignity as a woman. The both positions generate a number of questions about position of gender mainstream and its advocating.